Efektivitas Realisasi Anggaran Bidang Pembinaan Kemasyarakatan Desa Jajar Kecamatan Talun Kabupaten Blitar Tahun 2017 - Rita Kurniasari; Endah Masrunik; Anam Miftakhul Huda; Diana Elvianita (Jurnal Akuntansi dan Pajak, 2018)
The Village Fund Allocation is a part of the central and regional equity funds devoted to the village, one of which is for community development activities that include the fostering of education, peace and order, sports and arts, religion and health. In practice, the village government is required to run the field of community coaching efficiently and effectively to assess whether the village government can perform its duties properly in achieving the goals and objectives. This study aims to determine the effectiveness of budget realization of Village Fund Allocation for Community Development in Jajar Village Talun Sub-District, Blitar Regency, 2017. Data collected by observation method, library research, and documentation. Data analysis uses effectiveness and effectiveness ratio. The results of research on the effectiveness of budget realization of Village Fund Allocation for Community Development in Jajar Village Talun District, Blitar Regency in 2017 is at 90% -100% level and is included in the effective category. Level of effectiveness of budget realization Allocation of Village Fund of Community Development Field in Jajar Village year 2017 that is (98,55%). Based on the effectiveness of budget realization of Village Fund Allocation in the field of community cultivation in effective category, this means Jajar Village Government has optimized revenue or acceptance in applying the realization of budget ceiling Allocation of Village Funds in the field of community development by doing priority scale in determining expenditure budget to fit the expectations and objectives and benefits for quality in budget realization.